INDONESIAN ISLAMIC MODERNIST MOVEMENT:STUDY ON THE BACKGROUND OF ISLAMIC ORGANIZATION MUHAMMADIYAH - Mustakim, Muh.; Arifin, Syamsul; Hakim, Moh. Nur; In'am, Akhsanul; Tumin, Tumin (International Journal of Psychosocial Rehabilitation, 2020)
This paper describes the background of the birth of the Muhammadiyah organization as the Islamic Modernist movement in the early 20th century in Indonesia from the historical perspective and transformation theory approach as offered by Mochtar Bukhori which was constructed from a reprospective and prospective view so that it could see the reason of Muhammadiyah and the anticipatory view that was preached by the organization. The description of this writing shows that Muhammadiyah was born because of four main things, First, the condition of the Muslim society that is soluble in Tahayyul, Bid’ah and Khurafat. Secondly, the educational conditions of the nation’s children are trapped in ignorance and do not get the school’s opportunity in the policies of the Dutch colonial government that let it even conditioned on this retardation. third, socio-cultural conditions that require assistance, especially in the field of health and poverty alleviation. Furthermore, fourth, to care for the benefit of education, welfare and usefulness need an institutionalization in the form of organization to be strong, and continuously from generation to generation. The implications of the four backgrounds of Muhammadiyah’s emergence are hoped to be a major cornerstone for the organization’s mobilizer to consider the process sosio-historis the emergence of an organizational policy and visionary insight. Thus, it confirms a theory that the structured goodness will be more lasting and sustainable than the model of figurity that will be very easy to stop when it is gone.